Understanding Mis-implementation in Public Health Practice - Brownson, Ross C. (Am J Prev Med, 2015)
INTRODUCTION: A better understanding of mis-implementation in public health (ending effective programs and policies or continuing ineffective ones) may provide important information for decision makers. The purpose of this study is to describe the frequency and patterns in mis-implementation of programs in state and local health departments in the U.S. METHODS: A cross-sectional study of 944 public health practitioners was conducted. The sample included state (n=277) and local health department employees (n=398) and key partners from other agencies (n=269). Data were collected from October 2013 through June 2014 (analyzed in May through October 2014). Online survey questions focused on ending programs that should continue, continuing programs that should end, and reasons for endings. RESULTS: Among state health department employees, 36.5% reported that programs often or always end that should have continued, compared with 42.0% of respondents in local health departments and 38.3% of respondents working in other agencies. In contrast to ending programs that should have continued, 24.7% of state respondents reported programs often or always continuing when they should have ended, compared to 29.4% for local health departments and 25% of respondents working in other agencies. Certain reasons for program endings differed at the state versus local level (e.g., policy support, support from agency leadership), suggesting that actions to address mis-implementation are likely to vary. CONCLUSIONS: The current data suggest a need to focus on mis-implementation in public health practice in order to make the best use of scarce resources.